2015
DOI: 10.5056/jnm15151
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gastroesophageal Reflux Disease Using the Bravo Capsule pH System

Abstract: Gastroesophageal reflux disease (GERD) is a disease predominantly seen in the West but there is a rising trend in Asia. Ambulatory 24-hour catheter-based pH monitoring has been the de facto gold standard test for GERD that correlates symptoms with acid reflux episodes. However, drawbacks such as patients' discomfort, and catheter displacement render the test as cumbersome and errorprone. The Bravo pH wireless system is designed to be user-friendly and has an added advantage of prolonged pH monitoring. The syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 24 publications
(97 reference statements)
0
17
0
Order By: Relevance
“…The Bravo capsule was inserted orally using a delivery device under endoscopy guidance as previously described 13 . Usually, the Bravo capsule is placed 6 cm above the squamous‐columnar junction (SCJ) but in our study, we placed the capsule at the cardia where the acid‐pocket is situated, based on the technique previously published 14 .…”
Section: Methodsmentioning
confidence: 99%
“…The Bravo capsule was inserted orally using a delivery device under endoscopy guidance as previously described 13 . Usually, the Bravo capsule is placed 6 cm above the squamous‐columnar junction (SCJ) but in our study, we placed the capsule at the cardia where the acid‐pocket is situated, based on the technique previously published 14 .…”
Section: Methodsmentioning
confidence: 99%
“…While capsule endoscopes can be used to non‐invasively view the inflammation and lacerations from the acid reflux episodes, invasive catheter‐based pH monitoring is the standard diagnostic test for GERD. The Bravo pH wireless capsule system by Medtronic is less invasive and provides comparable diagnostic yields . However, the Bravo pH capsule still needs to be temporarily implanted and removed using an endoscope.…”
Section: Capsules For Robotic Sensingmentioning
confidence: 99%
“…FSSG score has been validated against the endoscopic findings in Japan with the cut-off score at 8 (FSSG score 8 or above), showed sensitivity of 62%, specificity 59% and accuracy of 60%. [12][13][14] Miyamoto et al found that high score FSSG is one of the factors related to failure of PPI monotherapy, in addition to female, alcohol consumption and obesity. Thus, GERD with a high FSSG score requiring PPI combination therapy with pro-kinetic drug for a more satisfactory outcome.…”
Section: Original Articlesmentioning
confidence: 99%